2016
DOI: 10.1007/s11469-016-9658-2
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use among University Students in South West Bank: Prevalence, Advantages and Disadvantages, and Association with Psychological Health

Abstract: University students are frequently using the Internet for educational purposes and for other purposes. Recently, there is a debate on advantages and disadvantages of Internet use and its effects on the students' psychological health. This study examines the prevalence of Internet use, its advantages and disadvantages, and its relationship with the psychological health of university students in the southern part of the West Bank. Mixed methods employing sequential exploratory design were used. Three focused gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Messias, Castro, Saini, Usman, and Peeples (2011) found that the sadness, suicidal ideation, and suicide attempts of young people were significantly higher in adolescents who played Internet or video games for 5 hr or more in a day. Although the Internet offers different advantages to the adolescents such as updating themselves, helping them in their works, solving their problems and establishing good relationships with others (Rayan et al, 2017), there is a risk of being affected by its unsupervised use especially for the individuals with low psychological health (Rayan et al, 2017) and adolescents (Kuss, van Rooij, Shorter, Griffiths & van de Mheen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Messias, Castro, Saini, Usman, and Peeples (2011) found that the sadness, suicidal ideation, and suicide attempts of young people were significantly higher in adolescents who played Internet or video games for 5 hr or more in a day. Although the Internet offers different advantages to the adolescents such as updating themselves, helping them in their works, solving their problems and establishing good relationships with others (Rayan et al, 2017), there is a risk of being affected by its unsupervised use especially for the individuals with low psychological health (Rayan et al, 2017) and adolescents (Kuss, van Rooij, Shorter, Griffiths & van de Mheen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(1) the Internet enables speed in communication, has an interactive character and is a support for learning (Spizzirri, Wagner, Mosmann, & Armani, 2012); (2) the Internet has become an important social context for older people as it influences their well-being, that is, by using the Internet they increase perceived levels of social support, reduce loneliness, improve life satisfaction and improve their psychological well-being (Heo, Chun, Lee, Lee, & Kim, 2015); (3) university students, in particular, can obtain many benefits from the use of the Internet for educational purposes (Rayan et al, 2017)-access to online journals, language learning, academic research, online library navigation (Al-Gamal, Alzayyat, & Ahmad, 2016)and also for relational purposes-navigation in social networks, online socialization and, even, establishing relationships (Jones, Johnson-Yale, Millermaier, & Pérez, 2009); (4) the Internet can be seen as an important means to increase life satisfaction among more fragile citizens and social groups-people of low economic levels and/or people suffering from health problems that interfere with the normal functioning of their daily life (Lissitsa & Chachashvili-Bolotin, 2016); (5) it can be used as a way to increase perceived social support, for example, through Facebook, which in turn decreases stress levels and increases psychological well-being. That is, Internet can be seen as an indirect benefit to health (Wiederhold, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the education system entirely, not partially as blended education, shifted to distance education as all educational tasks were achieved remotely. The entire shifted to online mode of education can cause social isolation, inability to manage time and organizing table of lessons, feeling confused and lack of self-motivation and face-to-face communication [ 68 ]. Therefore, they have a greater probability to feel stress, which causes fear, panic, anxiety, and depression due to accumulated educational tasks and the inability to achieve them.…”
Section: Discussionmentioning
confidence: 99%